The Influence of Islamic Bank Customer Experience and Perception on Brand Equity and Customer Satisfaction Customer Satisfaction - Prasetyo Harisandi; Ratih Hurriyati; Puspo Dirgantari; Engga Jalaludin (Yayasan Adra Karima Hubbi, 2023)
Background. This paper offers novelty in addressing the digitization trend and competitive challenges faced by banking service providers in achieving customer satisfaction in the digital economy ecosystem. It specifically focuses on customers of Bank Sya-riah Indonesia the leading Islamic banking company in Indonesia. The value of this paper lies in its insights for banking professionals, researchers, and policy makers in navigating the digital landscape and enhancing customer-centric digital banking services. Purpose. The population of this study consists of customers aged 18 years and over who use mobile banking services provided by Bank Syariah Indonesia, one of the largest Islamic banking companies in Indonesia in terms of market capitalization. Purposive sampling was used to obtain a sample of 160 respondents who met the research criteria. Method. This study uses quantitative methods with the type of experimental research that aims to examine the effect of using the Kinemaster application on the learning outcomes of Natural Science students in class VII UPT SMP Negeri 3 Pitu Riase. Results. The results of this study indicate that offline experience has no positive effect on brand image, other results online experience has a positive effect on brand im-age, and brand experience affects customer satisfaction, In addition, online experience is found to have a significant positive effect on offline experience. Conclusion. The findings of this study can provide valuable insights into the influence of offline and online experiences on brand equity and customer satisfaction with e-services in the Indonesian banking industry. This provides banks with a deeper understanding of consumer behavior and the important satisfaction factors that drive long-term decision-making in banking services.